High Open‐Circuit Voltage Cs2AgBiBr6 Carbon‐Based Perovskite Solar Cells via Green Processing of Ultrasonic Spray‐Coated Carbon Electrodes from Waste Tire Sources. Issue 22 (3rd November 2022) - Schmitz, Fabian; Lago, Nicolò; Fagiolari, Lucia; Burkhart, Julian; Cester, Andrea; Polo, Andrea; Prato, Mirko; Meneghesso, Gaudenzio; Gross, Silvia; Bella, Federico; Lamberti, Francesco; Gatti, Teresa
Abstract: Invited for this month cover is the group of Teresa Gatti at the Justus Liebig University (JLU) in Giessen, Germany, the group of Federico Bella at Politecnico di Torino (POLITO), Italy, and the group of Francesco Lamberti at the University of Padova (UNIPD), also in Italy. The image shows how waste tires can be converted in a conductive carbon powder that undergoes a green processing step to produce carbon electrodes for lead‐free perovskite solar cells. Similar devices can be employed to harvest indoor light in order to power the Internet of Things (IoT) ecosystem. The Research Article itself is available at 10.1002/cssc.202201590 . Abstract : "We will be able to make use of wasted light energy to provide electricity to our domestic sensing technologies…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202201590 . View the Front Cover here: 10.1002/cssc.202201928 .